Incorporating core concepts into an undergraduate neuroscience program in a resource-restricted environment - Stocker, Adam M.; Duncan, Chad S. (Frontiers in Education, 2024)
Recently, community-derived core concepts for neuroscience higher education were developed and published. These core concepts can serve as a valuable resource to ensure that a neuroscience-based educational program is not only concept-focused but also addresses the call for reform of higher education, as noted in the vision and change report. The number of undergraduate neuroscience programs is expanding throughout the nation, but unfortunately, the existing blueprints to design and launch such programs do not incorporate these core concepts. Furthermore, unpacking these core concepts in a resource-limited setting is logistically challenging. We reflected on the coverage of these core concepts within our existing neuroscience minor at a medium-sized, primarily residential, high undergraduate, public 4-year institution. In addition to assessing the number of community-derived core concepts addressed in our courses, our reflection discusses strategies for addressing challenges associated with (1) a departmental home for the program, (2) a meaningful student experience with limited resources, and (3) growing and developing the program into a minor, or from a minor into a major. These strategies may provide a roadmap for other institutions to launch or grow their own neuroscience program.